ACADEMIC DIFFICULTIES OF PRIMARY SCHOOL PUPILS OCCURRING DUE TO UNFAVOURABLE ENVIRONMENTAL FACTORS AND STRATEGIES TO OVERCOME THEM: THE EXPERIENCE OF PEDAGOGUES - Raudeliunaite, Rita; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The objective of the study presented in the article is to reveal academic difficulties of primary school pupils occurring due to unfavourable enviromental factors and the strategies to overcome them on the basis of the experience of pedagogues.  Problematic study question: What academic difficulties of pupils, which are resulted in by unfavourable enviromental factors, do primary school teachers encounter and how do they overcome them? Qualitative research type was chosen for the study. In the study, the method of a semi-structured interview was used. The study data were processed by using the method of content analysis. 12 pedagogues participated in the study.Academic difficulties of primary school pupils are resulted in by three groups of unfavourable enviromental factors: unfavourable factors related to their close environment (family) (the resolution of mutual problems in an inappropriate way, violence in close environment, emotionally cold relationships in their family, the lack of thoughtful and meaningful family leisure time, child's seclusion from one/both parent(s) due to various circumstances, the addiction of one/both parent(s), hypoguardianship and hyperguardianship), unfavourable factors within an educational institution (the mismatch between an educational programme and individual abilities and needs of a child, failure to involve a child in various activities, human and material resources of a school, unsafety of the school environment), unfavourable factors related to a peer group (rejection by peers, bullying, encouragement of a child to behave in a socially inappropriate manner).The study findings revealed that primary school teachers encounter the following academic difficulties: a lower level of a pupil's interest in his/her environment, the lack of knowledge and  experience, the lack of curiosity and inquisitiveness when  learning environment,  a  lower level of preparedness for school, attention retention problems, passivity when performing tasks, distrust / doubts regarding his/her abilities, fluctuation, regress or stagnation of a child's progress (learning achievements), reduced interest in learning and poor learning efforts when performing tasks, the lack of learning motivation, getting late to lessons or missing them.In order to overcome academic difficulties of pupils, teachers render them  individual assistance: they make the best use of the opportunities provided by their curriculum (they individualise and differentiate the learning in a lesson, provide consultations after lessons, if need be, they organise additional lessons), talk with a pupil about the learning difficulties arising to him/her and discuss strategies to overcome difficulties, set learning goals together with a pupils, rethink their teaching style, try various teaching methods, which correspond to a pupil's abilities and needs,  and enhance learning motivation, involve child's parents (guardians, custodians), and engage the specialists of educational assistance.